TINDAK TUTUR DIREKTIF GURU PENGGERAK TERHADAP SISWA DALAM PROSES PEMBELAJARAN DI SMPN 4 TAKALAR - Rahmayanti; Muhammad Saleh; Tuti Wijayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe 1) the use of directive speech acts by lead teachers towards pupils during the learning process at SMPN 4 Takalar. This study was conducted with two teachers, namely the Indonesian language lead teacher and the Civic Education teacher. Data collection techniques included observation, recording, listening, and note-taking. Data analysis employed three stages comprising data reduction, data presentation, and drawing conclusions. Data verification was carried out through expert and source triangulation. The research results indicate that: 1) the functions of directive speech acts used by the lead teacher towards students in the learning process at SMPN 4 Takalar revealed 10 functions of directive speech acts, with the questioning function being the most frequently observed. Meanwhile, in this study, the following functions were not found: requesting, pressuring, praying, inviting, dictating, stipulating, directing, approving, restricting, praying, desiring, suggesting, reminding, and advising.